2006
DOI: 10.1073/pnas.0511020103
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of γ-glutamyltranspeptidase from Escherichia coli , a key enzyme in glutathione metabolism, and its reaction intermediate

Abstract: ␥-Glutamyltranspeptidase (GGT) is a heterodimic enzyme that is generated from the precursor protein through posttranslational processing and catalyzes the hydrolysis of ␥-glutamyl bonds in ␥-glutamyl compounds such as glutathione and͞or the transfer of the ␥-glutamyl group to other amino acids and peptides. We have determined the crystal structure of GGT from Escherichia coli K-12 at 1.95 Å resolution. GGT has a stacked ␣␤␤␣ fold comprising the large and small subunits, similar to the folds seen in members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
212
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(223 citation statements)
references
References 39 publications
10
212
1
Order By: Relevance
“…Plasma cysteine levels of WT and GGT-knock-out mice were 12 μM and 2 μM, respectively (Lieberman et al, 1996), demonstrating that GGT is significant in cysteine recovery by initiating the cleavage of GSH into its constituent amino acids (Lieberman et al, 1996). Serum GGT is "mainly derived from the liver" (Okada et al, 2006). Elevated levels of serum GGT usually indicates hepatic damage, allowing for the use of GGT as a biomarker of liver damage (Okada et al, 2006;Heisterkamp et al, 2008).…”
Section: γ-Glutamyltransferasementioning
confidence: 99%
See 4 more Smart Citations
“…Plasma cysteine levels of WT and GGT-knock-out mice were 12 μM and 2 μM, respectively (Lieberman et al, 1996), demonstrating that GGT is significant in cysteine recovery by initiating the cleavage of GSH into its constituent amino acids (Lieberman et al, 1996). Serum GGT is "mainly derived from the liver" (Okada et al, 2006). Elevated levels of serum GGT usually indicates hepatic damage, allowing for the use of GGT as a biomarker of liver damage (Okada et al, 2006;Heisterkamp et al, 2008).…”
Section: γ-Glutamyltransferasementioning
confidence: 99%
“…Elevated levels of serum GGT usually indicates hepatic damage, allowing for the use of GGT as a biomarker of liver damage (Okada et al, 2006;Heisterkamp et al, 2008). GGT exhibits an αββα fold (Okada et al, 2006), as shown in Figure 3.…”
Section: γ-Glutamyltransferasementioning
confidence: 99%
See 3 more Smart Citations